1994
DOI: 10.1007/bf00443821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preservation and sterilization on cortical bone grafts

Abstract: The effects of preservation and sterilization on the structural properties of cortical bone were investigated. Specimens of cortical bone from rat tibiae were frozen (-70 degrees C for 28 days), freeze-dried, irradiated (1, 5, 25 and 50 kGy) or autoclaved (at 134 degrees C for 3 or 5 min), and examined by scanning electron microscopy. Cryopreservation and irradiation had no deleterious effects on the surface structure of the cortical bone. Freeze-drying caused microcracks running parallel to the mineralized fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
7

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 11 publications
3
23
0
7
Order By: Relevance
“…Munting et al (1988) found a loss of about half of the inductive capacity to be comparable to our results and to the findings of the classic study by Heiple et al (1963). In scanning electron microscopy, we found no deleterious effects of irradiation on the surface structure of cortical bone, whereas autoclaving caused a time-dependent swelling, detension and amalgamation of the fibrillary matrix (Voggenreiter et al 1994).…”
Section: Discussionsupporting
confidence: 92%
“…Munting et al (1988) found a loss of about half of the inductive capacity to be comparable to our results and to the findings of the classic study by Heiple et al (1963). In scanning electron microscopy, we found no deleterious effects of irradiation on the surface structure of cortical bone, whereas autoclaving caused a time-dependent swelling, detension and amalgamation of the fibrillary matrix (Voggenreiter et al 1994).…”
Section: Discussionsupporting
confidence: 92%
“…Corroborando os autores, igualmente não foram encontradas diferenças estatisticamente significativas entre os grupos GN e GCN quanto à resistência biomecânica, demonstrando que a desvitalização em nitrogênio líquido não compromete essa propriedade. Voggenreiter et al (1994) submeteram tíbias de ratos aos tratamentos de congelamento a -70°C, radiação gama, autoclavagem a 134°C por 3 e 5min e liofilização. Eles observaram os corpos de prova ao microscópio eletrônico e encontraram alterações na microestrutura das amostras autoclavadas e liofilizadas.…”
Section: Discussionunclassified
“…Extension of the autoclaving time from 3 to 5 min diminishes the bending load to 28%. Stiffness is also reduced by autoclaving [51,52]. This loss of biomechanical properties can be a problem for orthopaedic surgeons who need bones capable of supporting the weight of the body, but contrariwise in the skull the mechanical needs are minimal having only to support the scalp and prevent brain damage in case of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…There is bone marrow (BM) inside the graft. Haematoxiline- Eosine 40 • are lost during the autoclaving processes, probably because it does denaturalise the morphogenetic proteins [3,5,11,40,51]. Nakanishi et al [33] investigated whether bone inductive ability could be maintained in heat-treated bone, finding that it was maintained up to 70 ~ for 10 to 15 minutes, but not at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%